Tutupan Karang Keras dan Distribusi Karang Indikator di Perairan Aceh bagian Utara - Rudi, Edi (Biospecies, 2010)
Coral reefs are widely recognized as the center of coastal biological activity, coastal protection and geological processes, and also the productive site for fisheries and tourism. By definition, ecological resilience is the ability of a system to undergo, absorb and respond to change and disturbance, while maintaining its functions and controls. The environmental conditions that favor such community resilience may be different from those that favor resistance. From six field components of reef resilience, benthic cover and coral indicators population structure are the most important for reef resilience. This research has been done at 20 sites in northern Aceh reef, i.e. Weh Island (Sabang) and Aceh Besar regency. Benthic coverage data were collected by employing line intercept transects methods, whereas data of indicator coral population structure were collected by employing belt transect. The results show that hard coral ercentage were range from 20.46% - 67.4%. Generally, hard coral cover in areas protected by the Sabang Weh Island management authority was higher than those occurred in open access areas. The resistant corals category includes Porites (massive) and Pavona which are abundant in western Weh Island, while larger coral colonies of resistant category such as Acropora dan Pocillopora, are abundant in eastern Weh Island. If sea surface temperature is increase, west and north parts of the Weh Island will be the most vulnerable areas for coral mass bleaching.